Dampak Pemeliharaan Serta Pengoperasian Oily Water Separator Dalam Upaya Mencegah Pencemaran Laut Oleh Minyak Dari Kapal - Prihastuti, Ai Dewi; Abdurohman, Abdurohman; Thoriq, Wahyu Imam (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Impact of Maintenance and Operation of Oily Water Separators in Efforts to Prevent Marine Pollution by Oil from Ships. Environmental cleanliness is currently being given special attention by both developed and developing countries, and therefore has resulted in many regulations to maintain the balance of the ecosystem of life in this world. This imbalance can cause damage to the ecosystem due to pollution, one of which occurs in the ocean. This pollution is caused, among other things, by oil spills, toxic liquids, dangerous substances carried by sea in the form of packaging, rubbish from ships and air pollution. The aim of this research is to find out the pressure or procedures for operating the Oily Water Separator (OWS) aircraft correctly and according to procedures, as well as to find out how to maintain and repair the Oily Water Separator (OWS) aircraft, and why oily water planned operations may not occur. Separator (OWS). The method used in research is descriptive method. The data in this research were obtained from observations on the ship, documents obtained when conducting research on the ship, and from interviews. From the results of this research, data was obtained that against the background of the impact of maintenance and operation of the Oily Water Separator (OWS) in an effort to prevent marine pollution by oil from ships, it was stated that problems were discovered when carrying out research on the Oil Water Separator itself. The lack of air pressure would disrupt its operation. a three-way valve, as a whole, will disrupt the working system of the Oily Water Separator (OWS) water and oil separator. If the Oil Level Sensor which detects oil is found to be not working properly, it must be replaced with spare parts available on the ship. Apart from that, there is no regular operation of the Oil Water Separator, because problems arise on an aircraft because the operator does not carry out standard operating procedures. . To support work programs that comply with regulations, in this case it is necessary to standardize fundamentally and thoroughly regarding the implementation of standard operating procedures and be guided by the company's manual instruction book or PMS.